(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
The main objective of the research is to analyze the nature of the relationship between the independent variable (Enabling leadership) with its dimensions represented by (enhancing a sense of meaning in work, enhancing opportunities for participation in decision-making, confidence in high performance, independence from restrictions and bureaucracy) and the dependent variable (organizational prestige) with its dimensions represented by (Internal organizational prestige, external organizational prestige) in the Iraqi General Insurance Company. Accordingly, the hypothetical plan for the research was designed, which embodies the relationship between the research variables. The descriptive analytical approach was adopted and the questionnaire was used as the main tool for collecting data from a sample of (38) workers on sites Functional (higher, middle, executive), statistical methods were used to analyze the data (arithmetic mean, standard deviation, percentage weight, regression coefficient, coefficient of determination R², F test) and relying on the statistical program (SPSS), and the research concluded with a set of The most important results are the existence of a correlation and influence of empowering leadership with its dimensions in enhancing the organizational prestige of the researched company, which indicates the importance of the role of empowering leadership in restoring the prestige of the researched company by employing human, material and financial resources, improving the efficiency of its performance and increasing profitability.